Comparison of angioplasty and bypass surgery for critical limb ischaemia in patients with infrapopliteal peripheral artery disease. Issue 13 (21st September 2016) - Patel, S. D.; Biasi, L.; Paraskevopoulos, I.; Silickas, J.; Lea, T.; Diamantopoulos, A.; Katsanos, K.; Zayed, H.
Abstract: Background: Both infrapopliteal (IP) bypass surgery and percutaneous transluminal angioplasty have been shown to be effective in patients with critical limb ischaemia (CLI). The most appropriate method of revascularization has yet to be established, as no randomized trials have been reported. The aim of this study was to compare the outcomes of patients with similar characteristics treated using either revascularization method. Methods: Consecutive patients undergoing IP bypass and IP angioplasty for CLI (Rutherford 4–6) at a single institution were compared following propensity score matching. The study endpoints were primary, assisted primary and secondary patency, and amputation‐free survival at 12 months, calculated by Kaplan–Meier analysis. Results: Some 279 limbs in 243 patients were included in the study. The two groups differed significantly with respect to the incidence of diabetes ( P =  0·024), estimated glomerular filtration rate ( P =  0·006), total lesion length ( P  < 0·001) and Rutherford classification ( P =  0·008). These factors were used to construct the propensity score model, which yielded a matched cohort of 125 legs in each group. Primary patency (54·4 versus 51·4 per cent; P  = 0·014), assisted primary patency (77·5 versus 62·7 per cent; P  = 0·003), secondary patency (84·4 versus 65·8 per cent; P  < 0·001) and amputation‐free survival (78·7 versus 74·1 per cent; P =  0·043) were significantly better after bypass than angioplasty. However, limb salvage was similar (90·4 versus 94·2 per cent; P =  0·161), and overall complications (36·0 versus 21·6 per cent; P =  0·041) as well as length of hospital stay (18(4–134) versus 5(0–110); P  = 0·001) were worse in the surgical bypass group. Conclusion: There was no difference in limb salvage rates, but patency and amputation‐free survival rates were better 1 year after bypass surgery. Abstract : Randomized trials needed